The role of the university library in creating inclusive healthcare hackathons: A case study with design-thinking processes. (October 2019) - McGowan, Bethany
Librarians can utilize design-thinking practices to develop instructional materials, in the development of new products and services, and in prototyping novel solutions to problems. This paper will explore the role of design thinking in teaching and learning via the use of the Blended Librarians Adapted Addie Model (BLAAM), and will illustrate how well-designed learning approaches can be used to create inclusive learning environments. It will present a case study showcasing how an academic health sciences librarian utilized a design-thinking process to create a health data literacy instruction service that encourages diverse participation in healthcare hackathons.